Analysis of Moral Messages In The Poetry of Jahiliyah By Lubaid bin Rabiah - Hamdy, Mohammad Zainal; Shalihah, Asifatus (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
Literary works can have a big influence, one of which is poetry, one of the poems in ancient times was used to criticize politicians who only harmed the country because if expressed directly it was considered to be against and backfired on the government. This study was conducted to find out what moral messages are contained in the Syair jahiliyah by Lubaid bin Rabiah through analysis of the text and the words. The analysis was carried out on moral messages towards oneself as an individual, towards fellow human beings, and towards God the Creator. This study uses a Qualitative approach with the Type of Literature, and Data collection techniques using Documents and analyzed with componential data analysis. The results of the study showed that moral messages were found in the Syair jahiliyah by Lubaid bin Rabiah, namely having 3 moral messages, namely the relationship between humans and God with a moral subtotal of 3 times, the relationship between humans and other humans with a moral subtotal of 1 time, and the relationship between humans and themselves with a moral subtotal of 3 times. Second, the Syair jahiliyah by Lubaid bin Rabiah shows that every human being when experiencing sadness will tend to remember their God